Photodetectors: Mid‐Infrared Pyroresistive Graphene Detector on LiNbO3 (Advanced Optical Materials 4/2017). Issue 4 (February 2017) - Gopalan, Kavitha K.; Janner, Davide; Nanot, Sebastien; Parret, Romain; Lundeberg, Mark B.; Koppens, Frank H. L.; Pruneri, Valerio
Abstract : Graphene on a z ‐cut LiNbO3 pyroresistive platform allowing infrared light detection is reported by Frank H. L. Koppens, Valerio Pruneri, and co‐workers in article number 1600723. Light is absorbed in the LiNbO3 crystal substrate and the subsequent temperature increase, via the pyroelectric effect, induces polarization (bound) charges at the crystal surface. This causes doping into graphene, which, in turn, changes its carrier density and conductivity.